Digitally deployed, GP remote consultation video intervention that aims to reduce opioid prescribing in primary care: protocol for a mixed-methods evaluation. Issue 2 (6th February 2023) - Fu, Yu; Allen, Ben; Batterham, Alan M; Price, Christopher; Jones, Niki; Martin, Denis; Hex, Nick; Maule, Ewan; Finch, Tracy; Newton, Julia L; Ryan, Cormac G
Abstract : Introduction: Opioid prescribing rates are disproportionately high in the North of England. In addition to patients' complex health needs, clinician prescribing behaviour is also a key driver. Although strategies have been initiated to reduce opioid prescribing nationally, the COVID-19 pandemic has interrupted service provision and created challenges for the system and health professionals to tackle this complex issue. A pilot intervention using smartphone video messaging has been developed to remotely explain the rationale for opioid reduction and facilitate self-initiation of support. The aim of this study is to evaluate the potential benefits, risks and economic consequences of 'at scale' implementation. Methods and analysis: This will be a mixed-methods study comprising a quasi-experimental non-randomised before-and-after study and qualitative interviews. The intervention arm will comprise 50 General Practitioner (GP) Practices using System 1 (a clinical computer system hosting the intervention) who will deliver the video to their patients via text message. The control arm will comprise 50 practices using EMIS (a different computer system) who will continue usual care. Monthly practice level prescribing and consultation data will be observed for 6 months postintervention. A general linear model will be used to estimate the association between the exposure and the main outcome (opioid prescribing; average daily quantity (ADQ)/1000 specific therapeutic group age-sex related prescribing unit). Semi-structured interviews will be undertaken remotely with purposively selected participants including patients who received the video, and health professionals involved in sending out the videos and providing additional support. Interviews will be audio recorded, transcribed and analysed thematically. Ethics and dissemination: Ethics approval has been granted by the NHS Health Research Authority Research Ethics Committee (22/PR/0296). Findings will be disseminated to the participating sites, participants, and commissioners, and in peer-reviewed journals and academic conferences. Trial registration number: NCT05276089 .